2013
DOI: 10.1016/j.brainres.2013.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive excessive erythrocytosis causes inflammation and increased vascular permeability in aged mouse brain

Abstract: Excessive erythrocytosis results in severely increased blood viscosity that may compromise the vascular endothelium. Using our transgenic mouse model of excessive erythrocytosis we previously showed that despite altered brain endothelial cell morphology and an activated vasculature, brain vascular integrity was largely maintained up to 4-5 months of age. We now present data showing that persistent long-term damage of the vascular wall during the later stages of adulthood (9-10 months) results in a chronic detr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Similarly, a transgenic murine model of excessive erythrocytosis demonstrated co‐elevation of TNF‐α and IL‐6 within brain and plasma, concomitant with increased BBB permeability and reduced occludin expression (Ogunshola et al . ). Co‐elevated levels of TNF‐α and IL‐6 within the neurovascular unit has also been linked to cerebral infarction in rats (Sirén et al .…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, a transgenic murine model of excessive erythrocytosis demonstrated co‐elevation of TNF‐α and IL‐6 within brain and plasma, concomitant with increased BBB permeability and reduced occludin expression (Ogunshola et al . ). Co‐elevated levels of TNF‐α and IL‐6 within the neurovascular unit has also been linked to cerebral infarction in rats (Sirén et al .…”
Section: Discussionmentioning
confidence: 97%
“…Intracellular junctional proteins have been elucidated to maintain the cell-cell barrier [ 52 , 53 ]. Degradation of the AJ protein β -catenin [ 54 , 55 ] interferes with the sealing efficiency of ECs and results in barrier disruption. Our study revealed that activation of Sirt1 reversed LPS-sparked loss of β -catenin, while inactivation of Sirt1 exacerbated the effect.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR signalling can promote cancer stem cell growth and has been correlated with chemotherapy resistance of breast cancer cells with stem cell characteristics . In regards to the association of mTOR with other proliferative mechanisms, growth factors that rely upon mTOR signalling, such as EPO, may lead to cancer and blood–brain barrier injury during prolonged treatment regimens. Down‐stream signalling pathways of EPO, such as Wnt and WISP1, also can lead to unchecked cellular growth.…”
Section: Future Perspectivesmentioning
confidence: 99%